RATIONAL DRUG USE OF FACULTY MEMBERS WORKING AT A UNIVERSITY IN EASTERN TURKEY - Bulut, Aliye; YİĞİTBAŞ, Çağla; YILMAZ, Melek (Göbeklitepe Medical Science Journal, 2024)
The present study was conducted to determine the level of knowledge about rational drug use among the faculty members working at a university in the Eastern Anatolia region. The universe of the research consisted of faculty members at the central campus of a university in the Eastern Anatolia region, and 301 individuals participated in the research. A questionnaire form prepared by the researchers in line with the literature was used as a data collection tool. In the questionnaire, there are questions (32 items) that determine the socio-demographic characteristics of the participants and their level of knowledge about Rational Drug Use. In the statistical evaluations, number and percentage values and rank averages were given. Chi-square test was used in the research. Statistical significance level was taken as p<0.05. In the study, age range (χ2 = 7.928 p = 0.094), gender (χ2 = 3.110 p = 0.078), marital status (χ2 = 1.039 p = 0.308), academic title (χ2 = 3.734 p = 0.443), chronic disease status (χ2 = 2.170 p = 0.141) did not make a difference in terms of over-the-counter drug habit. It has been seen that the knowledge level about rational drug use of the faculty members working at a public university is not at the desired level and there are some deficiencies. It is essential to increase the rate of participation in in-service trainings and courses on rational drug use in order to raise awareness of the Rational Drug Use in all academicians working in both health-related and non-health-related fields.